2020
DOI: 10.3390/mi11040429
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Plastic Parts by Replication of Variable Pitch Laser-Induced Periodic Surface Structures

Abstract: Surface functionalization of plastic parts has been studied and developed for several applications. However, demand for the development of reliable and profitable manufacturing strategies is still high. Here we develop and characterize a new process chain for the versatile and cost-effective production of sub-micron textured plastic parts using laser ablation. The study includes the generation of different sub-micron structures on the surface of a mold using femtosecond laser ablation and vario-thermal micro-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…The surfaces appearing in nature (colored surfaces, anti-reflection surfaces, hydrophobic surfaces, wet and dry adhesion, and friction reduction) can be imitated [ 179 ] or the melt flow resistance in injection molding of polypropylene can be reduced [ 180 ]. LIPSS can be replicated as well on plastic parts [ 181 , 182 ]. The phenomena behind the creation of ripples is discussed in several publications [ 183 , 184 , 185 , 186 ].…”
Section: Applications Using Burst Pulsesmentioning
confidence: 99%
“…The surfaces appearing in nature (colored surfaces, anti-reflection surfaces, hydrophobic surfaces, wet and dry adhesion, and friction reduction) can be imitated [ 179 ] or the melt flow resistance in injection molding of polypropylene can be reduced [ 180 ]. LIPSS can be replicated as well on plastic parts [ 181 , 182 ]. The phenomena behind the creation of ripples is discussed in several publications [ 183 , 184 , 185 , 186 ].…”
Section: Applications Using Burst Pulsesmentioning
confidence: 99%
“…The texturing of polymeric parts can be achieved either via direct patterning or by replicating the surface of a tool with a specified topography, such as wood or leather [ 11 , 12 ]. It was found that certain textures could increase scratch resistance and conceal the surface damage of polymeric materials [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The replication quality of molded parts or even their mechanical properties can be improved by optimizing process parameters and controlling material flow. Therefore, an optimization approach has been used to improve the mechanical properties of the molded part made by polypropylene (PP) [ 4 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%